Advances in cancer research - Klein, George (Advances in cancer research ;, 2005)
The Advances in Cancer Research series provides invaluable information on the exciting and fast-moving field of cancer research. This volume presents outstanding and original reviews on a variety of topics including Molecular Mechanisms in Gliomagenesis; Activation of AKT Kinases in Cancer: Implications for Therapeutic Targeting; Mitochondria as Functional Targets of Proteins Coded by Human Tumor Viruses; Apoptotic Pathways and Therapy Resistance in Human Malignancies; Endostatin Signaling and Regulation of Endothelial Cell-Matrix Interactions; Molecular Mechanisms and Clinical Development.